ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI SIGNAL NASIONAL MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) (Studi Kasus : Badan Pendapatan Daerah Provinsi Riau (BAPENDA) - Arribe, Edo; Aryanto; Aulia, Sandra (Department of Information System Muhammadiyah University of Riau, 2022)
The National Signal application is a national digital Samsat application that can make it easier for the Indonesian people to make tax payments. The National Signal application, which will be held in Pekanbaru on August 25, 2021. Problems with the National Signal Samsat also often occur to some users of the National Signal application. The application requires a measurement of thelevel of end user satisfaction, so that it can find out the condition of application user satisfaction. This study has the aim of knowing user satisfaction using the EUCS method, this method is used because it is in accordance with the problems that existin the National Signal application users to make benchmarks on the dimensions that exist in the EUCS method. amount of 16%. While the other 4 variables have a high percentage of satisfaction with an average of 72-82%. And the results of the T test where the hypothesis on the accuracy variable section is rejected because there is no effect on users of the National Signal Application. Based on the overall results of the research, it can be seen that users of the National Signal application are satisfied withthe performance of the application with the highest score from the results of filling out the questionnaire from 222 samples which state that the National Signal Application is a complete information provider for paying the SAMSAT tax.